2006
DOI: 10.1038/nsmb1182
|View full text |Cite|
|
Sign up to set email alerts
|

Heme is involved in microRNA processing

Abstract: MicroRNAs (miRNAs) regulate the expression of a large number of protein-coding genes. Their primary transcripts (pri-miRNAs) have to undergo multiple processing steps to reach the functional form. Little is known about how the processing of miRNAs is modulated. Here we show that the RNA-binding protein DiGeorge critical region-8 (DGCR8), which is essential for the first processing step, is a heme-binding protein. The association with heme promotes dimerization of DGCR8. The heme-bound DGCR8 dimer seems to trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
316
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(344 citation statements)
references
References 50 publications
15
316
1
7
Order By: Relevance
“…We previously showed that the wild-type NC1 protein was fully occupied by heme when d-ALA was supplied in the bacterial cell culture at the time of induction, whereas about half of the total NC1 protein was present in a heme-free state when d-ALA was not added. 18 In the same study, we also found that mutation of Cys352 to an Ala, Ser, or His residue completely abolished heme binding to the NC1 protein expressed in bacteria.…”
Section: The Dimerization Domain Provides a Surface For Interaction Wmentioning
confidence: 56%
See 4 more Smart Citations
“…We previously showed that the wild-type NC1 protein was fully occupied by heme when d-ALA was supplied in the bacterial cell culture at the time of induction, whereas about half of the total NC1 protein was present in a heme-free state when d-ALA was not added. 18 In the same study, we also found that mutation of Cys352 to an Ala, Ser, or His residue completely abolished heme binding to the NC1 protein expressed in bacteria.…”
Section: The Dimerization Domain Provides a Surface For Interaction Wmentioning
confidence: 56%
“…6(A)] that interacted with heme in a way similar to the NC1 protein. 18 The purified HBD-His 6 was absorbed at peak wavelengths of 450, 367, and 556 nm [ Fig. 6(B)] and was a dimer bound by one heme molecule, as shown using ESI-MS [ Fig.…”
Section: The Dimerization Domain Is Embedded In An Independently Foldmentioning
confidence: 99%
See 3 more Smart Citations